Биоморфологическая структура флоры регионального ландшафтного парка “Донецкий кряж” - Остапко, В.М.; Гнатюк, Н.Ю. (Промышленная ботаника, 2006)
Quantitative species corellations in flora of the regional landscape park «Donetskiy kryazh» are given. They are adduced (after general habitus and plant life-cycle duration, rootage types, under- and above-ground shoots, etc.). Herbaceous policarpics (58,6%) and monocarpics (23,5%) prevail in biomorphological flora spectrum. Main root species (54,0%) and caudex species (31,7%) prevail on rootage type and under-ground shoots; non-rosellate species prevail over half-rosellate ones two times as much (64,5% and 32,3%) on above-ground shoots character. In the whole biomorphologic flora structure of the regional landscape park «Donetskiy kryazh» has the foreststeppe flora semblance of the easteuropean type with the mediterranean flora fraits.